Higher Education Timescapes: Temporal Understandings of Students and Learning. (October 2021) - Brooks, Rachel; Abrahams, Jessie; Gupta, Achala; Jayadeva, Sazana; Lažetić, Predrag
This article draws on data from six European countries (Denmark, England, Germany, Ireland, Poland and Spain) to explore the higher education timescapes inhabited by students. Despite arguments that degree-level study has become increasingly similar across Europe – because of global pressures and also specific initiatives such as the Bologna Process and the creation of a European Higher Education Area – it shows how such timescapes differed in important ways, largely by nation. These differences are then explained in terms of: the distinctive traditions of higher education still evident across the continent; the particular mechanisms through which degrees are funded; and the nature of recent national-level policy activity. The analysis thus speaks to debates about Europeanisation, as well as how we theorise the relationship between time and place.